"For my health and for my friends": Exploring motivation, sharing, environmentalism, resilience and class structure of food self-provisioning. Issue 106 (November 2019) - Ančić, Branko; Domazet, Mladen; Župarić-Iljić, Drago
Abstract: This article aims to supplement the growing understanding of the specificities of food self-provisioning (FSP) practice in Eastern Europe with deeper understanding of the class structure and broader environmentalist motivations of the self-reported practitioners. FSP and sharing of 'garden produce' is a long-term socioeconomic phenomenon in Croatia but so far there has been no research on the whole population in regard to FSP. We explore how widespread FSP in Croatia is, based on a survey of a nationally representative sample (N = 1000), within a broader social stratification project. We further explore the class structure of FSP practitioners and compare it to their reported motivations for engaging with the practice, and their pro-environmental behaviour, resilience and personal flourishing. Previous research in CEE has shown that FSP is characteristic of between 35% and 60% of national populations (Smith and Jehlička, 2013), whereas our findings show that a little over 50% of respondents claim that they have a garden, field or orchard, they use to produce food for themselves and part of their social network. As a practice it is more situated in smaller settlements and rural areas, but it is not a principally rural phenomenon. Slim majority of people involved in FSP in Croatia are identified as working class, however, FSP is not a coping strategy focused on the poor and low-income households in Croatia and food self-provisioners report higher level of personal wellbeing, more pro-environmental behaviour and higher level of self-perceived resilience.